PENGARUH DIMENSI KUALITAS LAYANAN TERHADAP KEPUASAN NASABAH DENGAN IMPLIKASI LOYALITAS PADA PT. BANK TABUNGAN PENSIUNAN NASIONAL, TBK CABANG KERTAJAYA SURABAYA - Bindi Febry Idham (STIE Perbanas Surabaya, 2013)
This study analyses the effect of the dimensions of service quality toward the satisfaction and its implication of the customers loyalty at PT Bank Tabungan Pensiunan Nasional (BTPN) Surabaya branch. It is a causal research using primary data gathered from the questionnaire filled by BTPNs 125 customers. The respondents were chosen using systematic random samplings due to the data of the customers have already been in the database of Personal Banking Officer (PBO). The result of this research indicates that the reliability, responsiveness, tangible are positively significant toward satisfaction, but assurance and empathy are not positively significant toward satisfaction, beside satisfaction is positively significant toward loyalty. Referring to the research result focusing on the weakness score of mean and the test result of hypotheses, some implications to BPTN are considerations in order to be able to provide better service quality such as in reliability and responsiveness in which there should be more strictly-time based service; in assurance and satisfaction there should better analysis to refer in controlling the service process; in empathy there should be on time in starting the counter; and in tangible there should be renew policy in the facilities.